2021
DOI: 10.29303/jppipa.v7i3.729
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Biochar and Combination of Inorganic Fertilizers and Biological Fertilizers in Increasing Yield and Levels of Brix Sorghum (Sorghum bicolor (L.) Moench) in Dry Land

Abstract: Research on the role of biochar, inorganic and biological fertilizers was aimed to increase crop yield and brix value of sorghum in dryland. This research was conducted from October 2020 to February 2021 at The Teaching Farm Soil Science Study Program, Akar-Akar Village, Bayan, North Lombok. The method used in this research is an experimental method, with the experimental plot in the field. The experiment consisted of two factors, was designed using a split-plot design. Biochar as the main plot with 2 treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…Nutrient-enriched biochar increases soil fertility, particularly in swamplands, lowering fertiliser use and environmental effects emissions while improving plant yield. Hawari et al, (2021) found that biochar without nutrients like nitrogen (N) did not boost crop yields. The atmosphere's CO2 content has risen steadily because more CO2 gas is entering than leaving.…”
Section: The Effect Of Palm Waste-based Additives On Swamp Land Soil ...mentioning
confidence: 99%
“…Nutrient-enriched biochar increases soil fertility, particularly in swamplands, lowering fertiliser use and environmental effects emissions while improving plant yield. Hawari et al, (2021) found that biochar without nutrients like nitrogen (N) did not boost crop yields. The atmosphere's CO2 content has risen steadily because more CO2 gas is entering than leaving.…”
Section: The Effect Of Palm Waste-based Additives On Swamp Land Soil ...mentioning
confidence: 99%